Turnover Rate of Autologous Plasma Fibrinogen-14C in Subjects with Coronary Thrombosis - Pilgeram, L. O (Thrombosis and Haemostasis, 1968)
The plasma concentration of fibrinogen increases as a statistical function of the occurrence of coronary heart disease. This increase in concentration is associated with a grossly enhanced rate of turnover of the molecule. A mean turnover rate of 0.260 mg/ ml/day of plasma fibrinogen in the young normal subject increases to 0.378 at 53 yrs of age in the normal group and to 0.466 in the same age group with coronary artery disease. The increased rate of turnover signifies an increase in both the rate of biosynthesis and the rate of utilization of the soluble precursor of the clot forming protein, fibrin.An increase in the concentration of plasma fibrinogen and in the rate of turnover also occur as a statistical function of age. Occurrence of occlusive vascular phenomenon in the same age group served to further enhance these changes. The regression data indicate that the metabolic changes are progressive and that the normal subject will eventually display, in association with the development of coronary thrombosis, a metabolic abnormality equivalent to the patient with coronary heart disease.Evidence is discussed which indicates that part or all of the enhanced utilization of fibrinogen may be attributed to an increase in the conversion of fibrinogen to fibrin. The relationship of the enhanced rate of turnover of fibrinogen to atherogenesis and thrombosis is reviewed.